Congenital Nasal Pyriform Aperture Stenosis as a rare manifestation of Trisome 8 Mosaicsm: a case report - Norhafizah Sahril,; Shifa Z,; Sitti Farhana J,; Marina MB, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Congenital Nasal Pyriform Aperture Stenosis (CNPAS) is an extremely rare cause of nasal airway obstruction. Clinically, it mimics choanal atresia in neonate. It needs to be differentiated because management differs from each. Pyriform aperture is located at the most anterior part of the nose and is always the narrowest region of the nasal cavity. Therefore, nasal obstruction can easily occur if there is slight decrease in its cross sectional area. CNPAS rarely presents alone. Usually, it arises together with a midline developmental defect such as holoprosencephaly or pituitary defect. We present the first ever reported case of CNPAS, in association with Trisomy 8 Mosaicsm (T8M).